PERSEPSI PESANGGEM MENGENAI HUTAN MANGROVE DAN PARTISIPASI PESANGGEM DALAM PENGELOLAAN TAMBAK MANGROVE RAMAH LINGKUNGAN MODEL EMPANG PARIT - Habibi Elhaq, Imam; Satria, Arif (Sodality: Jurnal Sosiologi Pedesaan, 2011)
This research was aimed to: (1) analyze perception of the pesanggem about mangrove forest; (2) analyze participation of the pesanggem in an Environmental Friendly Mangrove Embankment Empang-Parit Model Management; (3) analyze the correlation between perception and participation of pesanggem in mangrove embankment management. This research has been conducted by using survey method and supported by qualitative method with in-depth interview and observation. Qualitative method aimed to gain in-depth understanding related to the data which has been obtained from quantitative method. The result shows that most of the pesanggem has positif perception about mangrove forest ecosystem and ecology function of mangrove forest. Most of the pesanggem has negative perception about social-economy function of mangrove forest. Most of the pesanggem has low level participation in planning phase and monitoring phase. Most of the pesanggem has high level participation in implementation phase and benefitted phase.